Sodium titanate as basic catalyst in transesterification reactions - Marciniuk, Leticia L.; Hammer, Peter [UNESP]; Pastore, Heloise O.; Schuchardt, Ulf; Cardoso, Dilson (Elsevier B.V., 2014)
Sodium titanate was synthesized by the sol-gel method and characterized using X-ray diffraction, thermogravimetry-mass spectrometry, atomic absorption spectroscopy, scanning electron microscopy, energy-dispersive X-ray analysis and nitrogen physisorption. The non-calcined material was active as a catalyst in transesterification reactions and showed high stability. An appreciable loss of activity on the fourth reuse was accompanied by the appearance of a new species of oxygen and segregated sodium, identified by X-ray photoelectron spectroscopy (XPS). The XPS spectrum showed that the basic nature of the framework oxygen was inferior to the original basicity, which explained the decline in catalytic activity. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Sodium titanate; Sol-gel; Basicity; Transesterification; Heterogeneous catalysis